Exchanging terrorism oxygen for media airwaves the age of terroredia - Eid, Mahmoud (Advances in human and social aspects of technology (AHSAT) book series, 2014)
"This book presents a timely and thorough discussion on the integration of terrorism and the media, exploring the influence of traditional and new media on global terrorism"..